Rare preservation of Triassic pedorelicts with biogenic traces from a hot semi-arid upland palaeoenvironment at Portishead, SW England. Issue 6 (December 2022) - Howson, Mark P.; Tucker, Maurice E.; Whitaker, Fiona F.
Abstract: Pedorelicts occur sporadically in coastal exposures of Middle to Late Triassic continental sediments, at Portishead, SW England. The clasts include aeolian and bedrock constituents, calcrete textures, vesicles and other pedogenic features reflecting a hot semi-arid palaeoenvironment. Interpreted as being derived from an upland soil, they are classified in palaeosol terms as Calcic Protosol. In the most significant exposure, cryptic tubular trace fossils in branching networks occur within these pedorelict clasts in a localised fluvial deposit. This extremely rare palaeoecological archive offers a glimpse into continental upland life in a Pangaean desert landscape. It is documented for its own merit, to support continuing studies of its palaeobiology and to prompt investigation for comparable deposits. The pedorelicts occur within the Mercia Mudstone Marginal Facies (MMMF), close to its basal unconformity with underlying Paleozoic strata, at the margin of the Somerset Basin. The soil from which they are derived is interpreted to have developed in an upland regolith over Tournaisian bedrock of interbedded limestone and siltstone. These weathered and, with aeolian dust containing calcite and iron minerals and siliciclastic sand, formed a structured soil. This was aided by intermittent light and moderate rainfall that promoted mainly vadose pedogenic calcretization with displacive calcite crystallisation and siliciclastic grain breakage. In places, the soil was vesicular, as an 'Av' horizon, and in others, it was bioturbated with the development of calcite-lined tubules and unlined tunnels. At intervals of perhaps 10 4 to 10 5  years, catastrophic deluges eroded the regolith and transported clasts downslope towards the basin to form onlapping coarse clastic beds typical of the MMMF. The soil structure disintegrated but fragments that became pedorelicts were segregated in a fault-controlled palaeo-valley, possibly partly as a debris-flow, to be deposited as localised conglomeratic lenses with fluvial sand. After burial by further sedimentation, this deposit underwent diagenetic calcite cementation and baryte mineralisation before its present exposure by coastal erosion.